2016
DOI: 10.1007/s10151-016-1514-7
|View full text |Cite
|
Sign up to set email alerts
|

Surgical timing after chemoradiotherapy for rectal cancer, analysis of technique (STARRCAT): results of a feasibility multi-centre randomized controlled trial

Abstract: Background and Objectives: The optimal time of rectal resection after long-course

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…). A total of 26 publications, including four RCTs and 25 445 patients with rectal cancer were eligible for inclusion ( Table ). Twenty‐four of the 26 studies (22 650 patients) reported the primary endpoint of pCR based on the predefined wait interval and were included in the qualitative and quantitative analysis for this outcome variable; 15·9 per cent (1522 of 9551) and 11·3 per cent (1481 of 13 099) had achieved pCR in the extended and classical intervals respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…). A total of 26 publications, including four RCTs and 25 445 patients with rectal cancer were eligible for inclusion ( Table ). Twenty‐four of the 26 studies (22 650 patients) reported the primary endpoint of pCR based on the predefined wait interval and were included in the qualitative and quantitative analysis for this outcome variable; 15·9 per cent (1522 of 9551) and 11·3 per cent (1481 of 13 099) had achieved pCR in the extended and classical intervals respectively.…”
Section: Resultsmentioning
confidence: 99%
“…All patients underwent neoadjuvant 5FU‐based (5FU–capecitabine–folinic acid) nCRT, except in seven trials that included some patients treated with concomitant oxaliplatin (5 trials) or irinotecan (2) in addition to 5FU or had a proportion of patients who had nSCRT (1 trial). The number of participants in the included trials ranged from 31 to 16 915; apart from the RCTs and one phase II non‐randomized trial, all were retrospective or prospective observational series. Median follow‐up ranged from 14·25 months to 5 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…DNA damage may occur immediately with neoadjuvant chemotherapy (nCRT), however, cellular lysis only occurs in the weeks after irradiation, and regression is time dependent. In our study, we highlighted that the analysis was limited by the inclusion of only four RCTs and that subgroup analysis of RCTs exclusively did not demonstrate an enhanced pathological complete response (pCR) rate with the increased interval (odds ratio (OR) 1·15, 95 per cent c.i. 0·65 to 2·04; P = 0·63).…”
mentioning
confidence: 87%